Molecular dynamics simulation of microscopic friction mechanisms of amorphous polyethylene. Issue 43 (11th October 2019) - Zhan, Shengpeng; Xu, Haiping; Duan, Haitao; Pan, Lin; Jia, Dan; Tu, Jiesong; Liu, Lian; Li, Jian
Abstract : Determining the nature of microscopic mechanism of friction and wear by experimental method is a challenge. Molecular simulation technology is an effective method for exploring microscopic friction mechanisms of polymers. Abstract : Determining the nature of the microscopic mechanism of tribological properties by experimental methods for a polymer material surface/interface in the sliding friction process is a challenge. Molecular dynamics simulations were conducted by sliding a rigid indenter over the amorphous polyethylene. The results show that the friction is mainly composed of plough force and adhesion force. The average friction of adhesive contact is greater than that of frictionless contact because of the adhesion effect. The difference of average friction between adhesive contact and frictionless contact increases with increasing indentation depth because of the plough force effect. The elastic deformation of amorphous polyethylene in the cohesive zone is related to van der Waals interaction energy, whereas the plastic deformation was mainly dominated by bond angle energy and dihedral energy of the molecular chain for amorphous polyethylene. Molecular chains of amorphous polyethylene extend along the sliding direction and agglomerate along the indentation direction. The flexibility of the molecular chains increases with the increase of temperature and facilitates the molecular chains returning more easily to their original state.